Endoscopic suture fixation of gastrointestinal stents: proof of biomechanical principles and early clinical experience - Rieder, E.; Dunst, C. M.; Martinec, D. V.; Cassera, M. A.; Swanstrom, L. L. (Endoscopy, 2012)
Background and study aims: Gastrointestinal stents have become an important therapeutic option for several indications. However, migration in up to 40 % of cases represents a significant drawback, especially when covered prostheses are used. We hypothesized that a novel endoscopic suturing device could enable endoluminal stent fixation, which might increase attachment and thereby potentially reduce migration.Patients and methods: In an initial ex vivo porcine model, stents were attached to the esophageal wall with either endoscopic hemoclips or by endoscopic suture stent fixation (ESSF). The distal tension force required to induce dislocation was measured in Newtons (N) by a digital force gauge and was compared with conventional stent placement. ESSF was then performed clinically in five patients, in whom self-expanding metal stents were sutured in place for endoscopic treatment of gastrointestinal fistulas or strictures.Results: Esophageal ESSF was achieved in all experiments and significantly increased the force needed to displace the stent (n = 12; mean force 20.4 N; 95 % confidence interval [CI]: 15.4 – 25.4; P < 0.01) compared with clip fixation (n = 8; mean 6.1 N; 95 %CI 4.7 – 7.6) or stent placement without fixation (n = 16; mean 4.8 N; 95 %CI 4.0 – 5.6). All clinical cases of ESSF were performed successfully (5 /5) and took a median of 15 minutes. Elective stent removal was achieved without complications. One stent migration (1 /5) due to sutures being placed too superficially was observed. More loosely tied sutures remained intact, with the stent attached in place.Conclusion: Endoscopic suture fixation of gastrointestinal stents provided significantly enhanced migration resistance in an ex vivo setting. In addition, early clinical experience found ESSF to be technically feasible and easy to accomplish.